Speech by Prof. Daniel Mugendi, Principal Embu Uiniversity college to first year students - Mugendi, Daniel N. (My University, 2015)
Speech by Prof. Daniel Mugendi, Principal Embu Uiniversity college to first year students on Friday, May 8, 2015 at 9.00 a.m. in lecture hall one.
Keywords: Speech